Income Distribution: The Key to Earnings per Share. - Knutson, Peter H. (The Accounting Review, 1970)
Abstract The main purpose of this article has been to look rationally at the area of income reporting. Reporting of earnings per share has certainly been controversial and has even led to charges that it has created a chain letter growth effect in the absence of real growth. The reason for this has been that earnings, as reported today, are an odd mixture of income determination and income distribution and little effort has been made to distinguish between the two concepts. Moreover, income as reported on a per share basis has been allocated among an arbitrarily determined number of shares representing a combination of past, present, and future transactions. Finally, current reporting gives no recognition to the critical difference between cash distribution of earnings vis-a-vis earnings retained and its corollary, the two class method of computing earnings per share. The points raised by the Accounting Principles Board against the two-class method are precisely those which support it. The Board seems to have forgotten that the holder of a convertible security is free to exchange that security for common at any time and that the only reason for not doing so is that the value of the convertible is greater than the value of an equivalent number of shares of common.